In Search of Permanent Homes: Singapore's House Churches and the Politics of Space - Kong, Lily (Institutional Knowledge at Singapore Management University, 2002)
This paper focuses on one category of the 'unofficially sacred'-namely, those secular spaces which are used for worship and, in particular, residential spaces which are turned into 'house churches'. Using the case study of a house church in Singapore, the paper examines issues about the politics of religion in urban landscapes in a secular and simultaneously multireligious state. Contrary and in addition to current wisdoms about the politics of religious space, it is argued that various politics are observed: a politics of inclusion; a politics of hybridisation and in-betweenness; a politics of appropriation and nationalisation; and a politics of impermanence and precarity. Through this analysis, the paper seeks to bring added conceptual perspectives to the notion of 'sacred space' within the context of modern, urban, secular settings.